A new species of Loxosceles Heineken & Lowe, 1832 (Araneae: Sicariidae)from Iranian caves - Tahami, Mohadeseh S.; Zamani, Alireza; Sadeghi, Saber; Ribera, Carles (Zootaxa, 2017)
In this paper, a new spider species of the genus Loxosceles is described on the basis of morphological and molecular data. The phylogenetic relationship of the new species is discussed through the lens of molecular data (cox1, rrnL and H3 genes). Specimens were collected from three Iranian caves in the provinces of Fars, Yazd and Khuzestan, and the specimens showed morphological characteristics that allowed us to easily distinguish Loxosceles persica n. sp. from L. mrazig, which is its sister species, and from the cosmopolitan L. rufescens, which is a widely distributed species throughout the Mediterranean basin and the Middle East. It is the first Loxosceles species endemic to the Middle East.